Description of self care management in hypertension patients - Barus, Mardiati; Novitarum, Lilis; Sitinjak, Benedikta Sitinjak (Trigin Institute, 2023)
Hypertension or high blood pressure is often referred to as the silent killer because the patient does not know that he or she has hypertension. Hypertension is also known as heterogeneous group disease because it can affect anyone and various age, social, and economic groups. Hypertension is also the third biggest risk factor that causes premature death because it can trigger congestive heart failure and cerebrovascular disease. Self care management is an activity carried out by patients with the intention of improving one's well-being, because of their awareness of the time frame for maintaining life, continuing personal development and living a healthy functional life. The purpose of this study was to identify self care management in hypertensive patients at Santa Elisabeth Hospital Medan. This type of research is a descriptive research design with a cross sectional approach. Sampling in this study used a total sampling technique, the number of samples was 136 people. The results showed that self-care management in hypertensive patients was based on self-integrity with a sufficient category of 90 people (72.7%), self-care management in hypertensive patients based on self-regulation with a sufficient category of 66 people (48.5%), self-care management in hypertension patients based on interaction with other health workers with sufficient category as many as 77 people (56.6%), self care management in patients with hypertension based on monitoring other health workers sufficient category as many as 74 people (54.4%), self care management in hypertension patients based on compliance with the recommended rules category enough for 66 people (48.5%). It is hoped that health workers will improve the provision of health education for hypertensive patients, provide information to improve the quality of life of hypertensive patients by doing good self care management.